Age groups differences in the prevalence and popularity of individual tobacco product use in young adult and adult marijuana and tobacco co-users and tobacco-only users: Findings from Wave 4 of the population assessment of tobacco and health study. (1st April 2022) - Cohn, Amy M.; Chen, Sixia
Abstract: Background: Tobacco use is high among marijuana and tobacco users, compared to tobacco-only users. This study examined the relative ranking (based on prevalence) of past 30-day tobacco product use separately across young adult and older adult past 30-day marijuana and tobacco co-users and tobacco-only users. Method: Prevalence and relative ranking of past 30-day use of eight different tobacco products and blunts were examined in young adult (ages 18–24) and adults (ages 25 +) tobacco users who did and did not report past 30-day marijuana use (unweighted n = 33, 644) from Wave 4 of the Population Assessment of Tobacco and Health study. Multiple logistic regressions examined increased odds of using each product in the past 30-days by marijuana and tobacco co-use. Results: Nearly half (47.9%) of past 30-day young adult tobacco users reported past 30-day marijuana use (e.g., co-use); 27.7% of adult tobacco users reported past 30-day co-use. Cigarettes were the most popular product used in the past 30-days across tobacco-only and co-users of both age groups. Rankings of all other tobacco products differed between the age groups. Among young adult co-users, blunts were ranked the second most popular product used in the past 30-days, followed by e-cigarettes, and then cigarillos/filtered cigars. Among adult co-users, blunts were ranked the fourth most popular product used in the past 30-days. Adult co-users reported significantly higher prevalence of past 30-day use of all combustible products compared to tobacco only users. Conclusions: Co-users may be at increased risk of health consequences given high rates of combustible tobacco use. Highlights: A third of past 30-day tobacco users reported past 30-day marijuana use (co-use). Nearly half of past 30-day young adult tobacco users reported past 30-day marijuana use. Cigarettes were the most popular tobacco product among co-users of marijuana and tobacco. Blunts were the second most popular product among young adult co-users. Combustible tobacco use was higher in adult co-users than tobacco-only users.